Examining the Correlation between Critical Thinking and Problem-Solving Skills of Junior High School Students Against Climate Change - Anggie Siti Perdani; Hernani Hernani; Taufik Ramlan Ramalis (Jurnal Penelitian Pendidikan IPA, 2023)
This research examined the association between critical thinking and problem-solving skills among junior high school students, specifically focusing on Climate Change. The participants in this study included 272 students from XYZ Junior High School Rangkasbitung, comprising grades 8 and 9, during the even semester of the 2022/2023 academic year. A previously validated multiple-choice instrument with four answer choices assessed their abilities. The collected data were analyzed using SPSS 23 to determine the correlation and Winstep 5.4.1 for categorizing students' abilities. The findings revealed that the students obtained an average score of 42.82 for critical thinking and 43.53 for problem-solving skills. The correlation coefficient was calculated to be 0.74, indicating a strong and positive relationship between critical thinking and problem-solving skills. It was observed that an increase in the critical thinking score accompanied an increase in the problem-solving score. Additionally, the determination value of 0.546 indicated that critical thinking skills could explain 54.6% of the variance in problem-solving skills, while other factors influenced the remaining 45.4%.